Microencapsulation of Watermelon Rind Extract (Citrullus Lanatus) Using Maltodextrin and Gum Arabic as a Food Supplement Applications - Kusumaningrum, Maharani; Imani, Nadya Alfa Cahaya; Permanadewi, Indrasukma; Ardhiansyah, Hanif; Handayani, Dwi; Situmorang, Monatalia Lamtama; Rizkiyana, Luthfi; Audyaz-Zahra, Chealsy Zafarina; Indriawati, Aisya Eka (Jurnal Rekayasa Kimia & Lingkungan, 2025)
The food and beverage sector generates a large amount of organic waste, one of which is watermelon rind. Although it contains bioactive compounds such as lycopene, vitamin C, and phenolic compounds with antioxidant properties, watermelon rind is often discarded due to the rapid degradation of these compounds by light and temperature. This study proposes a solution to the aforementioned issue: the microencapsulation of watermelon rind (Citrullus lanatus) extract obtained through maceration. The process utilizes maltodextrin and gum arabic as coating materials and employs oven drying at temperatures of 45C, 50C, and 55C. The DPPH method evaluated strong antioxidant activity with an IC50 value of 70 ppm. Principal component analysis showed the content of Ethyl isoallocholate (31.80%), 5-Hydroxymethylfurfural (7.25%), 7,8-Epoxylanostan-11-ol, 3-acetoxy- (6.10%), and 2,4-Dihydroxy-2,5-dimethyl-3(2H)-furan-3-one (4.04%), where Ethyl isoallocholate inhibited DPPH radicals by 88%. The optimal formulation was achieved with an extract:solvent ratio of 20:80 and a maltodextrin and gum arabic ratio of 1:0, at 50C, yielding 81.161%. The microcapsules formed showed a spherical morphology, a smooth surface and showed small micro-cracks, and an average diameter between 20-80 m. Formulation with maltodextrin and gom arabic ratio of 3:4 at 55C produced the highest solubility (99.92%) and the lowest moisture content (0.97%). This study shows that microencapsulation is able to protect active compounds from degradation and has the potential to become a quality food supplement from natural ingredients, as well as supporting the reduction of organic waste and environmentalpreservation.